Pengaruh Model Pembelajaran dan Kemampuan Berpikir Kreatif Terhadap Hasil Belajar IPA Siswa SMP - Jhoni Lagun Siang; Moch. Sukardjo; Beatrix J.M. Salenussa; Yayan Sudrajat; Uswatun Khasanah (JTP - Jurnal Teknologi Pendidikan, 2020)
This study aims to determine the influence of learning models (Contextual Teaching and Learning and Quantum Learning) and the ability to think creatively about the learning outcomes of science education in junior high school students in SMPN 226 Jakarta. This research uses treatment design by level with sample number of 48 students at State Junior Secondary School (SMPN) 226 Jakarta. The data analysis was done by Analysis of Variance (ANAVA) two lane. The results showed that (1) Contextual Teaching and Learning model (CTL) was more effective in improving learning outcomes of IPA SMP Inclusion than Quantum Learning model (QL); (2) there was interaction effect between learning model and student's creative thinking ability toward science learning outcomes 3) for junior high school students in inclusion schools with high creative thinking skills more appropriately using Contextual Teaching and Learning models (CTL), (4) and for students with low creative thinking skills more appropriately using Quantum Learning models (QL).